Multi-aspheric description of the myopic cornea after different refractive treatments and its correlation with corneal higher order aberrations - Queirós, António (2012)
BACKGROUND: To analyse the asphericity of the anterior corneal surface (ACS) for different diameters, and correlate those values with corneal higher order aberrations (cHOA) before and after myopic treatments with corneal refractive therapy (CRT) for orthokeratology and customized (CL) and standard laser (SL) assisted in situ keratomileusis (LASIK). SETTING: Clínica Oftalmológica NovoVisión, Madrid, Spain. METHODS: The right eyes of 81 patients (27 in each treatment group), with a mean age of 29.94 ± 7.5 years, were analysed. Corneal videokeratographic data were used to obtain corneal asphericity (Q) for different corneal diameters from 3 to 8 mm and cHOA root mean square (RMS) obtained from Zernike polynomials for a pupil diameter of 6 mm. RESULTS: There were statistically significant differences in asphericity values calculated at different corneal diameters for different refractive treatments and their changes. The difference between asphericity at 3 and 8 mm reference diameters showed statistically significant correlations with spherical-like cHOA that was also significantly increased after all procedures. CONCLUSIONS: The shift in corneal asphericity and the differences among different treatment techniques are more evident for the smaller reference diameters. These differences can be much reduced or even masked for a peripheral reference point at 4 mm from centre, which is used by some corneal topographers.